2019
DOI: 10.15171/jhp.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Variation in yield and biochemical factors of German chamomile (Matricaria recutita L.) under foliar application of osmolytes and drought stress conditions

Abstract: Introduction: Chamomile is one of the oldest and most valuable medicinal plants from the Asteraceae family. In addition to pharmaceutical uses, its essential oil is extensively used in perfumery, cosmetics, food industry and aromatherapy. This experiment was conducted with the aim of investigating the effect of osmolytes foliar application on biochemical characteristics, and the yield of German chamomile under drought stress conditions. Methods: The experiment was conducted as a split plot with randomized comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This improvement in fruit yield per plant, fruit essential oil percentage and essential oil yield of coriander plants due to glycine betaine application would be resulted from the beneficial effect of glycine betaine on growth and metabolism and its role as an osmoprotectant. These results were relatively similar to that reported by Sadaghiani et al (2019) on chamomile. Also, selenium treatment resulted in an increase in fruit yield and that might be due to its role in increasing photosynthesis rate which causes more seed growth and conservation.…”
Section: Fruit Yield Fruit Essential Oil Percentage and Oil Yieldsupporting
confidence: 92%
“…This improvement in fruit yield per plant, fruit essential oil percentage and essential oil yield of coriander plants due to glycine betaine application would be resulted from the beneficial effect of glycine betaine on growth and metabolism and its role as an osmoprotectant. These results were relatively similar to that reported by Sadaghiani et al (2019) on chamomile. Also, selenium treatment resulted in an increase in fruit yield and that might be due to its role in increasing photosynthesis rate which causes more seed growth and conservation.…”
Section: Fruit Yield Fruit Essential Oil Percentage and Oil Yieldsupporting
confidence: 92%
“…Glycinebetaine functions as an osmotic adjustment substance and plays an important role in protecting the structure and function of proteins, enzymes, and cell membranes, thus enabling the plants to defend themselves against WS-induced oxidative damage [11,58]. Limit research has provided us limiting understanding of the differential role GB plays in the defense against drought and ooding stresses, even though GB has been applied in many plants under abiotic stress [22,23,39]. Therefore, the study was carried out to focus on the role of GB in various susceptible genotypes under either drought or ooding.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate stress damage and improve stress tolerance in plants, exogenous application of growth regulators has been widely adopted [21][22][23]. Glycinebetaine (GB), as a quaternary amine compound, is an osmolyte, which mainly is distributed in chloroplasts and cytoplasm [24] The GB acts as an osmotic adjustment substance and helps in enhancing the tolerance in crops against abiotic stress by increasing the antioxidant ability and protecting the biological membranes from oxidative stress caused by excess ROS [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Plant exudates that include L-tryptophan, the precursor to IAA, are found in nature (Quiroz-Villareal et al, 2012). Previous research has demonstrated that amino acids can affect a plant's physiological activity either directly or indirectly (Sadaghiani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%